Comparison of saccadic eye movements and facility of ocular accommodation in female volleyball players and non-players - Jafarzadehpur, E.; Aazami, N.; Bolouri, B. (Scandinavian Journal of Medicine & Science in Sports, 2007)
There is controversy on the interaction of sport exercise and visual functions. Some aspects of visual skills have been evaluated in volleyball players.